O gerenciamento de pesquisas fármaco-clínicas no Brasil - Costa, Sidney de Brito (1988)
The author reviews international and national literature on the subject, describes the several phasEs for the research and development of a new drug and critically analyses the management of such research. lhe author also d.scusses the positionlng of clinicaI pharmacology and pharmaceutical medicine in Brazil and another countries, pointing out lhe difilculties for performing and conducting lhe research, and proposes a new managerial approach for controlled clinicaI trials, using drugs. After a twelve-year period , from 1975 to 1987, acting in the several areas of the medicaI departament of some pharmaceutical industries, with more than 80% of this time devoted to the planning, implementation, monitoring, conclusion and publication of clinicaI trials, lhe author was responsible for the publication of 15 papers, having some kind of participatíon in at least 24 more clinicai studies already published and 31 to be published (attachment 3). The author, after a situation analusis, proposes a new method for the management of clinical research carried out in Brazil, in such a way that alI the steps needed for conduling such research are methodized, planned and evaluated accordingly, including the possibility of storing information for prompt retrieval at any time, so establishing a data bank for several types of information, íncluding those of public nature.